(untitled) (Bangladesh Journal of Agricultural Research, 2008)
The present study was conducted in Jessore and Gazipur districts during 2002-2003 to assess the socio-economic status of plant nursery business in Bangladesh. A total of 40 private plant nurseries, four government nurseries (BADC) and six NGO nurseries (BRAC) were selected for the study. The study revealed that 60% of the private nursery owners had secondary level of education and 50% owners performed their business on leased land. More than 55% owners had 6-10 years of experience in nursery business. This business has vast potentials of generating employment and income of the owners. The yearly net returns per ha for private, government, and NGO nursery were Tk. 215766, Tk. 120149, and Tk. 535961, respectively. The rates of returns over full-cost were found to be 1.43 for private, 1.37 for government, and 1.50 for NGO nurseries. Non-availability of improved seeds/seedlings was the main constraint for private and NGO nurseries, whereas lack of adequate fund was the crucial problem for government nurseries. DOI: http://dx.doi.org/10.3329/bjar.v32i3.539 Bangladesh J. Agril. Res. 32(3) : 375-385, September 2007